Students’ Perception: Coffee Shop as Joyful Learning Space in Improving English Speaking Skill: Anxiety, comfortable place, Internal motivation, external motivation, joyful learning - Authar, Nailul; Saputri, Tiyas; Djuwari, Djuwari (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Learning English requires a special condition so that the learners can learn English, especially speaking skill, without anxiety. For that reason, preparing a comfortable place is essential for making the learners motivated to learn or at least to make them like English. This study attempts to explore the students of the customers in a coffee shop to learn English informally. It took 4 respondents of the coffee shop, at Djuw Cafe, selected by purposive sampling with the criteria as the loyal customers who very often come to the coffee shop. They were interview unintentionally with unstructured interview and observation by the researcher. The interview was also done with the owner of the coffee shop. These sources of data then interpreted and classified into the domain with the themes based on the semantic meanings. These themes then were analyzed and interpreted, and finally drawn the inferences for conclusion. It was found that the most essential factor that makes the respondents highly motivated to learn English is the listening of English songs. Secondly, they are motivated to enjoy learning English through the written English expressions that are decorated on the walls. Therefore, making the learners motivated to learn English, it requires a comfortable place with a specific design of the place with English songs and some written English expression for the decoration on the wall.